Polymer electrolyte membrane and preparation method and application thereof
By introducing metal single atoms into metal organic frame materials and compounding with polymer and electrolyte salts to form polymer electrolyte membranes, the problems of low ionic conductivity and poor stability to metal lithium anode at room temperature are solved. , achieving high performance and low temperature adaptability of high-energy density lithium batteries.
Patent Information
- Application Number
- CN202411439238.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-11
AI Technical Summary
The existing polyethylene oxide (PEO)-based solid electrolyte has low ionic conductivity at room temperature and poor stability to metal lithium anodes, which limits its application in high-energy density lithium batteries.
By introducing metal single atoms into the metal organic frame material and loading them in polymer fibers, it is compounded with the polymer and electrolyte salts to form a polymer electrolyte membrane. This film promotes rapid conduction of alkali metal ions in the abundant pores in metal organic frame materials, and improves ionic conductivity and interface stability.
It significantly improves the room temperature lithium ion conductivity, thermal stability and electrochemical stability of the polymer electrolyte membrane, and the electrochemical stability window expands to 1-5V, which is suitable for high-energy density lithium batteries and maintains excellent performance in low temperature environments.
Smart Images

Figure HDA0005085912840000011 
Figure HDA0005085912840000012 
Figure HDA0005085912840000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a polymer electrolyte membrane and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid growth of demand for high energy density and high safety rechargeable batteries, solid electrolyte technology has received widespread attention. Compared with traditional organic liquid electrolytes, solid electrolytes have higher safety, better electrochemical stability and the advantage of avoiding leakage. Therefore, solid electrolytes occupy an important position in the research and development of solid-state lithium batteries. By using solid electrolytes instead of liquid electrolytes, not only can the safety performance of lithium batteries be significantly improved, but also many problems existing in traditional electrolytes can be overcome, such as flammability and safety hazards caused by electrolyte leakage.
[0003] Solid electrolytes are generally divided into three categories: polymer solid electrolytes, inorganic solid electrolytes, and composite solid electrolytes. Polymer solid electrolytes have become a hot topic of current research due to their excellent flexibility, good film-forming properties, and excellent interface compatibility with electrode materials. Among them, polyethylene oxide (PEO)-based polymer solid electrolytes are a typical polymer system that can conduct lithium ions. This system forms an ion-conducting channel for the migration of lithium ions in the polymer matrix through the interaction between PEO and lithium salts. However, PEO-based solid electrolytes exhibit low ionic conductivity at room temperature, which seriously restricts their application in high-energy-density lithium batteries. In addition, PEO-based solid electrolytes have poor stability to metal lithium anodes, which easily causes interfacial instability problems in batteries, further limiting their widespread application.
[0004] In order to solve these problems, researchers have proposed a variety of modification methods, including chemical cross-linking, copolymerization modification, and filling nanoparticles, to improve the ionic conductivity and interface stability of polymer solid electrolytes. However, these methods usually have problems such as complex processes and increased costs, making them difficult to be widely promoted in practical applications. Summary of the invention
[0005] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a polymer electrolyte membrane. The polymer electrolyte membrane is formed by introducing metal single atoms into a metal organic framework material, loading the metal single atoms into a polymer fiber, and then compounding the polymer with an electrolyte salt to form a polymer electrolyte membrane having high room temperature lithium ion conductivity, thermal stability and electrochemical stability.
[0006] The second object of the present invention is to provide a method for preparing a polymer electrolyte membrane. The method comprises the following steps: mixing and reacting the raw materials for preparing metal single atoms with the raw materials for preparing metal organic framework materials, so that the metal single atoms are loaded in the metal organic framework materials, and then electrospinning the metal single atoms together with the materials for preparing polymer fibers, so that the metal organic framework materials loaded with metal single atoms are evenly distributed in the polymer electrolyte membrane, which is beneficial to improving the performance of the prepared polymer electrolyte membrane.
[0007] The third object of the present invention is to provide a battery, which uses the polymer electrolyte membrane of the present invention as the electrolyte layer, effectively improving the battery's ionic conductivity, cycle stability, low-temperature performance, etc., so that it can meet the application requirements of higher energy density and more stringent working environment.
[0008] A fourth object of the present invention is to provide application of the above-mentioned polymer electrolyte membrane and / or the preparation method of the above-mentioned polymer electrolyte membrane in the field of batteries or flexible electronic devices.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first aspect of the present invention provides a polymer electrolyte membrane, comprising a nanofiber membrane, a polymer and an electrolyte salt; the polymer and the electrolyte salt are distributed in the nanofiber membrane; the nanofiber membrane comprises a polymer fiber and a metal-organic framework material carrying metal single atoms; the metal single atoms are loaded in the metal-organic framework material through coordination bonds, and the metal-organic framework material is distributed in the polymer fiber.
[0011] The present invention introduces metal single atoms into the metal organic framework material. The metal single atoms are used to promote the dissociation of alkali metal ions in the electrolyte salt. The abundant pores in the metal organic framework material provide fast alkali metal ion conduction channels, thereby improving the ionic conductivity of the polymer electrolyte membrane. In addition, the introduction of the metal organic framework material loaded with metal single atoms into the polymer electrolyte membrane can effectively inhibit the growth of lithium dendrites and the like, and extend the cycle life of the battery. Compared with the prior art, the present invention introduces metal single atoms into the polymer electrolyte membrane for the first time, which significantly improves the electrochemical properties of the polymer electrolyte membrane, especially the low temperature performance and cycle performance.
[0012] The performance of polymer electrolyte membranes has been significantly improved. Specifically, the ionic conductivity at room temperature has increased by 10% compared with that of traditional PEO electrolytes. -7 S cm -1 Increase to 10 -3 S cm -1 , the electrochemical stability window is extended to 1-5V, while maintaining good thermal stability and low-temperature performance.
[0013] Preferably, the metal organic framework material (ie, MOF) is selected from at least one of the following: ZIF organic framework materials (such as ZIF-8, ZIF-7, ZIF-5, ZIF-11, ZIF-67), COF organic framework materials (such as TpPa-1, COF-1, COF-2, COF-4, COF-5, COF-6, COF-8, COF-10, COF-14, COF-16, COF-18, COF-20, COF-22, COF-42, COF-43, COF-63, COF-102, COF- The organic framework materials of the present invention are as follows: COF-103, COF-105, COF-108, COF-202, COF-300, COF-303, COF-316, COF-318, COF-320, COF-366, COF-367, COF-505), HOF-1, HOF-2, HOF-3, HOF-4, HOF-5, HOF-6, HOF-7, HOF-8, HOF-9, HOF-10, HOF-11, HOF-100, HOF-101, HOF-102, HOF-14). ZIF-based organic framework materials are metal organic framework materials with high specific surface area and diverse pore structures. They can effectively load metal single atoms and provide sufficient ion transport paths. COF-based organic framework materials are connected by strong covalent bonds and have good chemical and thermal stability. They are excellent candidate materials for metal single atom loading. HOF-type organic framework materials use hydrogen bonds to form a stable structure. They can adjust the size and shape of the framework pores by regulating intermolecular hydrogen bonds, making them suitable for single metal atom loading under specific environments.
[0014] Preferably, the metal single atom is selected from at least one of the following: titanium and vanadium.
[0015] Preferably, the polymer is selected from at least one of the following: polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyacrylate (such as polymethyl methacrylate PMMA), polyether sulfone (PES), polyvinyl alcohol (PVA), polyetherimide (PEI).
[0016] Preferably, the electrolyte salt is selected from at least one of the following: alkali metal salts of bistrifluoromethanesulfonyl imide, alkali metal salts of hexafluorophosphate, alkali metal salts of bis(fluorooxalate)borate, alkali metal salts of perchlorate, alkali metal salts of hexafluoroarsenate, alkali metal salts of tetrafluoroborate, alkali metal salts of dioxalatoborate, and alkali metal salts of trifluoromethanesulfonate.
[0017] Preferably, the material of the polymer fiber includes at least one of the following: polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), poly 1,3-dioxolane (POM), polyamide (PA), polytetrafluoroethylene (PTFE), and polycarbonate (PC).
[0018] Preferably, the mass ratio of the polymer to the electrolyte salt is 1:(0.15-2.4), for example, it can be selected from: 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4.
[0019] Preferably, the mass of the metal-organic framework material loaded with metal single atoms is 5.5-45% of the mass of the nanofiber membrane, for example, it can be selected from 5.5%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 45%.
[0020] Preferably, the material of the polymer fiber includes polyacrylonitrile and polyvinylidene fluoride-hexafluoropropylene; the mass ratio of polyacrylonitrile to polyvinylidene fluoride-hexafluoropropylene is (0.6-9):1, for example, it can be selected from: 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1.
[0021] Preferably, the polymer electrolyte membrane has a thickness of 20 to 30 μm, for example, selected from: 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm.
[0022] The second aspect of the present invention provides a method for preparing the polymer electrolyte membrane according to the first aspect of the present invention, comprising the following steps:
[0023] S1: mixing raw materials for preparing metal single atoms and raw materials for preparing metal organic framework materials to obtain metal organic framework materials loaded with metal single atoms;
[0024] S2: preparing a nanofiber membrane by electrospinning a spinning solution comprising the metal organic framework material loaded with metal single atoms and a preparation material of the polymer fiber;
[0025] S3: Filling the nanofiber membrane with a mixed solution including a polymer and an electrolyte salt to prepare the polymer electrolyte membrane.
[0026] Step S1 in the present invention achieves a one-pot method for preparing a metal-organic framework material loaded with metal single atoms by mixing and reacting the raw materials for preparing metal single atoms with the raw materials for preparing a metal-organic framework material, so that the metal single atoms are in situ loaded inside the metal-organic framework material. This step can uniformly load the metal single atoms in the metal-organic framework material.
[0027] Step S2 in the present invention prepares a nanofiber membrane by blending the metal organic framework material loaded with metal single atoms and the preparation material of the polymer fiber and then electrospinning them together. This step can make the metal organic framework material loaded with metal single atoms evenly distributed in the nanofiber membrane and the particles are uniform, which is beneficial to improving the overall performance of the polymer electrolyte membrane.
[0028] In step S3 of the present invention, the polymer and the electrolyte salt are directly filled into the interior of the nanofiber membrane. On the one hand, the nanofiber membrane can play a supporting role. On the other hand, the presence of the nanofiber membrane can construct a transmission channel network for alkali metal ions, so that the alkali metal ions can be quickly and efficiently conducted in the polymer electrolyte membrane, thereby improving the ionic conductivity and ion migration amount of the polymer electrolyte membrane.
[0029] Preferably, when the metal single atom is Ti and the metal organic framework material is ZIF-8, the step S1 is: titanium salt, zinc salt, dimethylimidazole and solvent are mixed and reacted to obtain ZIF-8 material loaded with Ti single atom; further preferably, when the metal single atom is Ti and the metal organic framework material is ZIF-8, the step S1 is: titanium salt, zinc salt, dimethylimidazole and solvent are mixed and reacted, centrifuged and dried to obtain ZIF-8 material loaded with Ti single atom.
[0030] Preferably, the titanium salt is selected from at least one of titanium acetylacetonate, titanium tetrachloride, titanium isopropoxide and titanium sulfate.
[0031] Preferably, the zinc salt is selected from at least one of zinc nitrate hexahydrate, zinc chloride and zinc sulfate.
[0032] Preferably, the molar ratio of the titanium salt to the zinc salt is 1:(5-20), for example, it can be selected from: 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20.
[0033] Preferably, the solvent is selected from at least one of tetrahydrofuran, N,N-dimethylformamide (DMF) and methanol.
[0034] Preferably, in the mixed solution comprising the polymer and the electrolyte salt, the ratio of the total mass of the polymer and the electrolyte salt to the mass of the solvent is 1:(22-100), for example, can be selected from 1:22, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60, 1:65, 1:70, 1:75, 1:80, 1:85, 1:90, 1:100.
[0035] Preferably, the mixing reaction is specifically: ultrasonic stirring at 15-40° C. for 2-24 hours.
[0036] Preferably, the voltage of the electrospinning is 10 to 20 kV, the flow rate of the spinning solution is 0.013 to 0.1 mL / min, and the electrospinning receiving distance is 5 to 15 cm. The electrospinning conditions of the present invention can make the metal organic framework material uniformly dispersed in the nanofiber membrane. By adjusting the voltage, flow rate and receiving distance of the electrospinning, the diameter and porosity of the nanofibers can also be regulated to further optimize the electrochemical properties of the polymer electrolyte membrane.
[0037] Preferably, the step S3 is: filling the nanofiber membrane with a mixed solution including a polymer and an electrolyte salt, and vacuum drying to obtain the polymer electrolyte membrane.
[0038] Preferably, the vacuum drying temperature is 55-65°C.
[0039] Preferably, the vacuum drying time is 10 to 24 hours.
[0040] The third aspect of the present invention provides a battery comprising the polymer electrolyte membrane according to the first aspect of the present invention.
[0041] Preferably, the battery comprises a positive electrode, a polymer electrolyte membrane and a negative electrode arranged in sequence; the positive electrode contains a positive electrode active substance; the positive electrode active substance comprises an alkali metal iron phosphate, an alkali metal cobaltate, a high-nickel ternary material or sulfur.
[0042] Preferably, the high nickel ternary material comprises LiNi 0.9 Co 0.05 Mn 0.05O2.
[0043] Preferably, the battery includes a lithium metal battery, a sodium metal battery, a potassium metal battery, a sulfide solid-state battery, an oxide solid-state battery, and a soft-pack battery.
[0044] Preferably, the working temperature of the battery is -30 to 30° C. The battery in the present invention is adaptable to a variety of working environments: the battery exhibits excellent stability both at a low temperature of -30° C. and at a room temperature of 30° C., meeting a wide range of application requirements.
[0045] Preferably, the negative electrode is metallic lithium or graphite.
[0046] The fourth aspect of the present invention provides the use of the polymer electrolyte membrane described in the first aspect of the present invention and / or the preparation method described in the second aspect of the present invention in the field of batteries or flexible electronic devices.
[0047] The beneficial effects of the present invention are as follows: the polymer electrolyte membrane of the present invention significantly improves the lithium ion conductivity, thermal stability and electrochemical stability at room temperature by introducing metal single atoms into the metal organic framework material. Specifically, the polymer electrolyte membrane still has good stability when the temperature reaches 200°C, the decomposition temperature exceeds 200°C, the electrochemical stability window is 1 to 5V, and the lithium ion conductivity is as high as 1.25mS cm -1 In addition, the polymer electrolyte membrane of the present invention has a wide range of applications and can be adapted to lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), ultra-high nickel ternary positive electrode materials (LiNi 0.9 Co 0.05 Mn 0.05 O2), sulfur (S) and other positive electrode materials.
[0048] The battery of the present invention adopts the polymer electrolyte membrane of the present invention, so that the battery has high ionic conductivity, high stability and safety, excellent cycle performance, and still has a high capacity retention rate at a low temperature of -30°C. In extreme cases such as overcharging and overdischarging, it can still maintain high safety and avoid thermal runaway, so that it can meet the application requirements of higher energy density and more stringent working environment. After optimization, the battery can still maintain a capacity retention rate of more than 98% at a low temperature of -30°C; after 2000 cycles at a rate of 10C, the capacity retention rate is not less than 90%, the capacity retention rate after 3000 cycles is not less than 80%, and the capacity retention rate after 5000 cycles is not less than 70%. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is the surface morphology of ZIF-8@Ti prepared in Example 1.
[0050] Figure 2These are the high-resolution spherical aberration-corrected STEM images and XAFS test images of ZIF-8@Ti prepared in Example 1.
[0051] Figure 3 This is the SEM image of the ZIF-8@Ti fiber prepared in Example 1.
[0052] Figure 4 Surface and cross-sectional SEM images of the polymer electrolyte membrane prepared in Example 1.
[0053] Figure 5 The electrochemical stability window and lithium ion conductivity test diagrams of the polymer electrolyte membranes in Examples 1-2 and Comparative Examples 1-2.
[0054] Figure 6 It is the LSV curve test diagram of the polymer electrolyte membrane in Examples 1-2 and Comparative Examples 1-2.
[0055] Figure 7 This is a time-current curve test diagram of the polymer electrolyte membrane in Example 1.
[0056] Figure 8 2 are the EIS graphs of the polymer electrolyte membrane in Example 1 at the initial state and the steady state.
[0057] Fig. 9 These are test diagrams of the burning experiment of the polymer electrolyte membranes in Example 1 and Comparative Example 1.
[0058] Fig.10 Graphs of thermogravimetric analysis of the polymer electrolyte membranes in Example 1 and Comparative Example 1.
[0059] Fig.11 2 are DSC graphs of the polymer electrolyte membranes in Example 1 and Comparative Examples 1-2.
[0060] Fig.12 This is a rate performance test diagram of a battery assembled from the polymer electrolyte membranes in Examples 1 to 2 and Comparative Example 1.
[0061] Fig.13 This is a test diagram of the cycle performance of a lithium metal symmetric battery assembled with the polymer electrolyte membranes of Examples 1 to 2 and Comparative Example 1.
[0062] Fig.14 This is a graph showing the long cycle performance test of a battery assembled with the polymer electrolyte membrane in Example 1 at 10C.
[0063] Fig.15 This is a graph showing the cycle performance of a battery assembled with the polymer electrolyte membrane in Example 1 at -30°C.
[0064] Fig.16This is a test diagram of the cycle performance of the soft-pack battery assembled with the polymer electrolyte membrane in Example 1 at 0.5C.
[0065] Fig.17 The capacity-voltage curve of a battery assembled from the polymer electrolyte membrane of Example 1 and a sulfur positive electrode at 0.2C.
[0066] Fig.18 The capacity-voltage curve of a battery assembled from the polymer electrolyte membrane of Example 1 and a lithium cobalt oxide positive electrode at 0.1C is shown.
[0067] Fig.19 The capacity-voltage curve of the battery assembled with the polymer electrolyte membrane of Example 1 and the NCM91 positive electrode at 0.1C. DETAILED DESCRIPTION
[0068] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0069] Example 1
[0070] This example provides a method for preparing a polymer electrolyte membrane, which comprises the following steps:
[0071] Synthesis of ZIF-8@Ti
[0072] 1. Raw material preparation:
[0073] (1) Metal precursor: titanium acetylacetonate (C 10 H 14 O5Ti) and zinc nitrate hexahydrate (Zn(NO3)2·6H2O); ligand: dimethylimidazole (C5H8N2).
[0074] (2) Solvents: 1) Framework synthesis solvents: N,N-dimethylacetamide (DMF), tetrahydrofuran (THF), methanol (MeOH), all reagents were analytical grade and purchased from Sigma-Aldrich.
[0075] 2. Formula ratio: (1) The molar ratio of titanium acetylacetonate to zinc nitrate hexahydrate is 1:10. (2) The molar ratio of dimethylimidazole to solvent (DMF and methanol) is 1:2.
[0076] 3. Synthesis steps:
[0077] (1) Preparation of Solution A: 5 g of titanium acetylacetonate and 10 g of zinc nitrate hexahydrate were dissolved in a mixed solvent of 100 ml of tetrahydrofuran and 50 ml of methanol (the volume ratio of tetrahydrofuran to methanol was 2:1), and ultrasonically treated for 5 minutes to ensure uniform dissolution, thereby forming Solution A.
[0078] (2) Preparation of Solution B: Dissolve dimethylimidazole in DMF and methanol, and perform ultrasonic treatment for 5 minutes to form Solution B.
[0079] (3) Reaction mixing: 50 ml of solution A was slowly added dropwise to 200 ml of solution B, and stirring was maintained on a magnetic stirrer. The reaction temperature was controlled at 30° C. After the addition was completed, the mixture was placed in a 45° C. thermostat for 8 hours.
[0080] (4) Post-treatment: The reaction product was centrifuged at 4000 rpm for 10 minutes, and then washed with methanol three times. The washed sample was dried in a vacuum oven at 60°C for 12 hours to obtain ZIF-8@Ti powder, thereby introducing titanium metal single atoms into the ZIF-8 framework.
[0081] Preparation of ZIF-8@Ti nanofibers
[0082] 1. Raw material preparation: ZIF-8@Ti; polymer substrate: polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP); solvent: N,N-dimethylacetamide (DMF), used to dissolve the polymer substrate.
[0083] 2. Formula ratio: The mass ratio of ZIF-8@Ti, PAN and PVDF-HFP is 1:8:2.
[0084] 3. Preparation steps:
[0085] (1) Preparation of solution: 0.5 g of PAN and 0.5 g of PVDF-HFP were added to 10 ml of DMF solvent and stirred to completely dissolve them to form a uniform polymer solution. Subsequently, 1 g of ZIF-8@Ti powder was slowly added to the above polymer solution with a stirring speed of 1500 rpm for 48 h to ensure that the ZIF-8@Ti powder was uniformly dispersed in the polymer solution to obtain a mixed solution.
[0086] (2) Electrospinning process: The mixed solution is placed in the syringe of the electrospinning equipment, and a high voltage electric field is used to eject the solution to form nanofibers. The spinning voltage is set to 20KV, and the liquid propulsion speed is 0.013mL / min. The fiber collection during the spinning process is carried out by a drum collection method, the speed of the drum is controlled at 300rpm, and the distance between the spinning needle and the drum is 10cm. The collected nanofibers are post-treated in a vacuum drying oven at 60°C to remove the solvent and obtain uniform ZIF-8@Ti composite nanofibers.
[0087] Preparation of SPE@ZIF-8@Ti composite polymer electrolyte
[0088] 1. Raw material preparation: ZIF-8@Ti composite nanofibers; polymer electrolyte matrix: polyethylene oxide (PEO); lithium salt: lithium trifluoromethanesulfonyl imide (LiTFSI); solvent: acetonitrile (ACN), used to dissolve PEO-based polymers.
[0089] 2. Formula ratio: The mass ratio of ZIF-8@Ti composite nanofibers, PEO and LiTFSI is as follows: ZIF-8@Ti composite nanofibers: PEO: LiTFSI = 2:1:1.
[0090] 3. Preparation steps:
[0091] (1) Preparation of solution: PEO is dissolved in acetonitrile and stirred to form a polymer solution; then, LiTFSI lithium salt is added to the solution according to a proportion and stirred until the lithium salt is completely dissolved to obtain a polymer / lithium salt solution.
[0092] (2) Film casting process: ZIF-8@Ti composite nanofibers are covered on a polytetrafluoroethylene plate, and then the polymer / lithium salt solution is dripped into the nanofibers and allowed to stand in an argon glove box for 30 minutes to form a film. After the film is formed, it is placed in a 60°C vacuum drying oven to dry and remove the solvent to obtain the polymer electrolyte membrane in this example, namely the SPE@ZIF-8@Ti composite polymer electrolyte membrane.
[0093] Example 2
[0094] This example provides a method for preparing a polymer electrolyte membrane, which comprises the following steps:
[0095] Synthesis of ZIF-8@V
[0096] 1. Raw material preparation:
[0097] (1) Metal precursor: Vanadium acetylacetonate (C 10 H 14O5V) and zinc nitrate hexahydrate (Zn(NO3)2·6H2O). Ligand: dimethylimidazole (C5H8N2).
[0098] (2) Solvents: Synthesis framework solvents: N,N-dimethylacetamide (DMF), tetrahydrofuran (THF), methanol (MeOH). All reagents were analytical grade and purchased from Sigma-Aldrich.
[0099] 2. Formula ratio: The molar ratio of vanadium to zinc atoms in vanadium acetylacetonate and zinc nitrate hexahydrate is 1:10.
[0100] 3. Synthesis steps:
[0101] (1) Preparation of Solution A: 0.1 g of vanadium acetylacetonate and 9 g of zinc nitrate hexahydrate were dissolved in a mixed solvent of 50 ml of tetrahydrofuran and 20 ml of methanol, and ultrasonicated for 5 minutes to ensure uniform dissolution, thereby forming Solution A.
[0102] (2) Preparation of Solution B: 12 g of dimethylimidazole was dissolved in 30 ml of DMF and 10 ml of methanol and subjected to ultrasonic treatment for 5 minutes to form Solution B.
[0103] (3) Reaction mixing: Solution A was slowly added dropwise to solution B, and stirring was maintained on a magnetic stirrer. The reaction temperature was controlled at 30° C. The addition process lasted for 30 minutes. After the reaction, the mixture was placed in a 45° C. thermostat for 8 hours.
[0104] (4) Post-treatment: The reaction product was centrifuged at 4000 rpm for 10 minutes, and then washed three times with 50 ml of methanol. The washed sample was dried in a vacuum oven at 60 °C for 12 hours to obtain ZIF-8@V powder, thereby introducing vanadium metal single atoms into the ZIF-8 framework.
[0105] Preparation of ZIF-8@V nanofibers
[0106] 1. Raw material preparation: ZIF-8@V powder; polymer substrate: polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP); solvent: N,N-dimethylacetamide (DMF), used to dissolve the polymer substrate.
[0107] 2. Formula ratio: The mass ratio of ZIF-8@V to PAN and PVDF-HFP is 1:8:2.
[0108] 3. Preparation steps:
[0109] (1) Preparation of solution: PAN and PVDF-HFP were added to DMF solvent in proportion and stirred to completely dissolve them to form a uniform polymer solution; then, ZIF-8@V powder was slowly added to the above polymer solution with a stirring speed of 1500 rpm for 48 hours to ensure that the ZIF-8@V powder was uniformly dispersed in the solution to obtain a mixed solution.
[0110] (2) Electrospinning process: The mixed solution is placed in the syringe of the electrospinning equipment, and a high voltage electric field is used to eject the solution to form nanofibers. The spinning voltage is set to 20KV, and the liquid propulsion speed is 0.013mL / min. The fiber collection during the spinning process is carried out by a drum collection method, the speed of the drum is controlled at 300rpm, and the distance between the spinning needle and the drum is 10cm. The collected nanofibers are post-treated in a vacuum drying oven at 60°C to remove the solvent and obtain uniform ZIF-8@V composite nanofibers.
[0111] Preparation of SPE@ZIF-8@V composite polymer electrolyte
[0112] 1. Raw material preparation: ZIF-8@V composite nanofibers; polymer electrolyte matrix: polyethylene oxide (PEO); lithium salt: lithium trifluoromethanesulfonyl imide (LiTFSI); solvent: acetonitrile (ACN), used to dissolve PEO-based polymers.
[0113] 2. Formula ratio: The mass ratio of ZIF-8@V composite nanofibers, PEO and LiTFSI is as follows: ZIF-8@V composite nanofibers: PEO: LiTFSI = 2:1:1.
[0114] 3. Preparation steps:
[0115] (1) Preparation of solution: PEO is dissolved in acetonitrile and stirred to form a polymer solution; then, LiTFSI lithium salt is added to the solution according to a proportion and stirred until the lithium salt is completely dissolved to obtain a polymer / lithium salt solution.
[0116] (2) Film casting process: ZIF-8@V nanofibers are covered on a polytetrafluoroethylene plate, and then the polymer / lithium salt solution is dripped into the nanofibers and allowed to stand in an argon glove box for 30 minutes to form a film; after the film is formed, it is placed in a 60°C vacuum drying oven to dry and remove the solvent to obtain a SPE@ZIF-8@V composite polymer electrolyte membrane.
[0117] Example 3
[0118] This example provides a method for preparing a polymer electrolyte membrane, comprising the following steps:
[0119] (1) First, the COF covalent metal organic framework material is synthesized according to the method in (J.Am.Chem.Soc.2022,144,17097-17109). In this step, after the COF is synthesized, the metal single atoms are loaded into the framework structure of the COF through a subsequent loading process.
[0120] (2) Acetylacetonate titanium and COF covalent metal organic framework were reacted by solvothermal method at 120°C for 24 h to introduce titanium atoms into the pores of COF covalent metal organic framework to obtain COF@Ti;
[0121] (3) COF@Ti was used instead of ZIF-8@Ti in Example 1, and the polymer electrolyte membrane in this example was prepared according to the preparation method in Example 1.
[0122] Example 4
[0123] This example provides a method for preparing a polymer electrolyte membrane, comprising the following steps:
[0124] (1) First, the COF covalent organic framework material is synthesized according to the method in (J.Am.Chem.Soc.2022,144,17097-17109). In this step, after the COF is synthesized, the metal single atoms are loaded into the framework structure of the COF through a subsequent loading process.
[0125] (2) Acetylacetonate vanadium and COF covalent metal organic framework were reacted by solvothermal method at 120°C for 24 h to introduce single vanadium atoms into the pores of COF covalent metal organic framework to obtain COF@V;
[0126] (3) COF@V was used instead of ZIF-8@Ti in Example 1, and the polymer electrolyte membrane in this example was prepared according to the preparation method in Example 1.
[0127] Example 5
[0128] This example provides a method for preparing a polymer electrolyte membrane, comprising the following steps:
[0129] (1) First, the HOF covalent metal organic framework was synthesized according to the preparation method in the prior art (Adv. Funct. Mater. 2023, 33, 2211631);
[0130] (2) Titanium acetylacetonate and HOF covalent metal organic framework were reacted by solvothermal method at 120°C for 24 h to introduce titanium atoms into the pores of HOF covalent metal organic framework to obtain HOF@Ti;
[0131] (3) HOF@Ti was used instead of ZIF-8@Ti in Example 1, and the polymer electrolyte membrane in this example was prepared according to the preparation method in Example 1.
[0132] Example 6
[0133] This example provides a method for preparing a polymer electrolyte membrane, comprising the following steps:
[0134] (1) First, the HOF covalent metal organic framework was synthesized according to the preparation method in the prior art (Adv. Funct. Mater. 2023, 33, 2211631);
[0135] (2) Acetylacetonate vanadium and HOF covalent metal organic framework were reacted by solvothermal method at 120°C for 24 h to introduce single vanadium atoms into the pores of HOF covalent metal organic framework to obtain HOF@V;
[0136] (3) HOF@V was used to replace ZIF-8@Ti in Example 1, and the polymer electrolyte membrane in this example was prepared according to the preparation method in Example 1.
[0137] Example 7
[0138] The preparation method of the polymer electrolyte membrane in this example is different from that in Example 1 only in that the same amount of lithium hexafluorophosphate (LiPF6) is used to replace the LiTFSI lithium salt in Example 1.
[0139] Example 8
[0140] The preparation method of the polymer electrolyte membrane in this example is different from that in Example 1 only in that the same amount of lithium difluoro(oxalato)borate (LiDFOB) is used to replace the LiTFSI lithium salt in Example 1.
[0141] Example 9
[0142] This example provides a solid-state lithium metal battery, which includes a positive electrode material, a negative electrode material and any one of the polymer electrolyte membranes of Examples 1 to 8 of the present invention.
[0143] The positive electrode material can be lithium iron phosphate (LFP), lithium cobalt oxide (LCO), high nickel ternary material (NCM) or sulfur (S); the negative electrode material: metal lithium sheet.
[0144] The assembly steps of the solid-state lithium metal battery in this example are as follows: 1) Place the positive electrode, composite polymer electrolyte membrane and metal lithium sheet in order, add metal gasket, spring and battery shell, and seal at a pressure of 100MPa in a sealing machine. 2) All assembly processes are carried out in an inert gas atmosphere to prevent oxidation of the electrolyte and metal lithium.
[0145] Example 10
[0146] This example provides a solid-state sodium metal battery, which includes a positive electrode material, a negative electrode material and any one of the polymer electrolyte membranes of Examples 1 to 8 of the present invention.
[0147] The positive electrode material can be sodium iron phosphate (NVP) or sodium cobalt oxide (NaCoO2); the negative electrode material is a metallic sodium sheet; the electrolyte salt uses sodium trifluoromethanesulfonimide (NaTFSI) as the sodium salt in the electrolyte to optimize ionic conductivity and interface stability.
[0148] The assembly steps of the solid-state sodium metal battery in this example are: 1) Its assembly steps are similar to those of lithium metal batteries, but the positive electrode material is replaced with a sodium-based material and the negative electrode material is replaced with a metal sodium sheet; 2) NaTFSI is used as the sodium salt in the electrolyte membrane to ensure the good electrochemical performance and stability of the sodium metal battery.
[0149] Embodiment 11
[0150] This example provides a solid-state potassium metal battery, which includes a positive electrode material, a negative electrode material and any one of the polymer electrolyte membranes of Examples 1 to 8 of the present invention.
[0151] The positive electrode material uses potassium iron phosphate (KFePO4) or potassium cobalt oxide (KCoO2); the negative electrode material uses metallic potassium sheet; the electrolyte salt uses potassium trifluoromethanesulfonyl imide (KTFSI) as the potassium salt in the electrolyte to ensure efficient potassium ion conduction.
[0152] The assembly steps of the solid-state potassium metal battery in this example are as follows: Its assembly steps are similar to those of lithium metal batteries, but the positive electrode material is replaced with a potassium-based material and the negative electrode material is replaced with a metallic potassium sheet. KTFSI is used as a potassium salt in the electrolyte membrane to optimize the ionic conductivity and electrochemical stability of the potassium metal battery.
[0153] Example 12
[0154] This example provides a solid-state lithium metal soft-pack battery package, and the packaging material is an aluminum-plastic film.
[0155] Assembly process: The positive and negative electrodes of the soft pack battery are aluminum tabs and nickel tabs, respectively. The positive electrode is LFP or NCM, and the negative electrode is metallic lithium. Use any polymer electrolyte membrane in Examples 1 to 8 as the electrolyte layer, stack the positive electrode, the negative electrode and the electrolyte membrane, and finally package them with aluminum plastic film. During the packaging process, ensure that the inside of the battery core is dry and vacuum to prevent decomposition of the electrolyte and oxidation of the positive and negative electrode materials.
[0156] It can be seen from Examples 9 to 12 that the composite polymer electrolyte membrane of the present invention exhibits broad application potential in a variety of new solid-state batteries.
[0157] Therefore, in addition to being used in solid-state lithium metal batteries, the polymer electrolyte membrane of the present invention is also suitable for: (1) All-solid-state batteries formed by inorganic compounds: such as oxide solid-state batteries, sulfide solid-state batteries, etc., by optimizing the structure and material composition of the electrolyte membrane to improve the ionic conductivity and interface stability of the battery. (2) Sodium ion batteries: The composite polymer electrolyte membrane of the present invention is also suitable for the development of sodium ion batteries, providing a new material option for the low-cost, high-performance application of sodium ion batteries. (3) Flexible electronic devices: Since the electrolyte membrane of the present invention has good mechanical strength, thin thickness and flexibility, it is suitable for various flexible electronic devices, such as wearable devices, flexible display screens, flexible energy storage devices, etc. This material can not only ensure the performance stability of the equipment, but also adapt to multiple bending and stretching, and has broad application prospects.
[0158] Comparative Example 1
[0159] This example provides a method for preparing a polymer electrolyte membrane, which comprises the following steps:
[0160] Synthesis of ZIF-8
[0161] 1. Raw material preparation:
[0162] (1) Metal precursor: zinc nitrate hexahydrate (Zn(NO3)2·6H2O); ligand: dimethylimidazole (C5H8N2).
[0163] (2) Solvents: 1) Framework synthesis solvents: N,N-dimethylacetamide (DMF), tetrahydrofuran (THF), methanol (MeOH), all reagents were analytical grade and purchased from Sigma-Aldrich.
[0164] 2. Formula ratio: The molar ratio of dimethylimidazole to solvent (DMF and methanol) is 1:2.
[0165] 3. Synthesis steps:
[0166] (1) Preparation of Solution A: 0.1 g of vanadium acetylacetonate and 9 g of zinc nitrate hexahydrate were dissolved in a mixed solvent of 50 ml of tetrahydrofuran and 20 ml of methanol, and ultrasonicated for 5 minutes to ensure uniform dissolution, thereby forming Solution A.
[0167] (2) Preparation of Solution B: 12 g of dimethylimidazole was dissolved in 30 ml of DMF and 10 ml of methanol and subjected to ultrasonic treatment for 5 minutes to form Solution B.
[0168] (3) Reaction mixing: Solution A was slowly added dropwise to solution B, and stirring was maintained on a magnetic stirrer. The reaction temperature was controlled at 30° C. The addition process lasted for 30 minutes. After the reaction, the mixture was placed in a 45° C. thermostat for 8 hours.
[0169] (4) Post-treatment: The reaction product was centrifuged at 4000 rpm for 10 minutes, and then washed with methanol three times. The washed sample was dried in a vacuum oven at 60° C. for 12 hours to obtain ZIF-8 powder.
[0170] Preparation of ZIF-8 nanofibers
[0171] 1. Raw material preparation: ZIF-8; polymer substrate: polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP); solvent: N,N-dimethylacetamide (DMF), used to dissolve the polymer substrate.
[0172] 2. Formula ratio: The mass ratio of ZIF-8 to PAN and PVDF-HFP is 1:8:2.
[0173] 3. Preparation steps:
[0174] (1) Preparation of solution: PAN and PVDF-HFP were added to DMF solvent in proportion and stirred to completely dissolve them to form a uniform polymer solution; then, ZIF-8 powder was slowly added to the above polymer solution with a stirring speed of 1500 rpm for 48 hours to ensure uniform dispersion of ZIF-8 powder in the solution.
[0175] (2) Electrospinning process: The mixed solution is placed in the syringe of the electrospinning equipment, and a high voltage electric field is used to eject the solution to form nanofibers. The spinning voltage is set to 20KV, and the liquid propulsion speed is 0.013mL / min. The fiber collection during the spinning process is carried out by a drum collection method, the speed of the drum is controlled at 300rpm, and the distance between the spinning needle and the drum is 10cm. The collected nanofibers are post-treated in a vacuum drying oven at 60°C to remove the solvent and obtain uniform ZIF-8 composite nanofibers.
[0176] Preparation of SPE@ZIF-8 composite polymer electrolyte
[0177] 1. Raw material preparation: ZIF-8 nanofibers; polymer electrolyte matrix: polyethylene oxide (PEO); lithium salt: lithium trifluoromethanesulfonyl imide (LiTFSI); solvent: acetonitrile (ACN), used to dissolve PEO-based polymers.
[0178] 2. Formula ratio: The mass ratio of ZIF-8 nanofibers to PEO and LiTFSI is: ZIF-8 nanofibers: PEO: LiTFSI = 2:1:1.
[0179] 3. Preparation steps:
[0180] (1) Preparation of solution: PEO is dissolved in acetonitrile and stirred to form a polymer solution; then, LiTFSI lithium salt is added to the solution according to a proportion and stirred until the lithium salt is completely dissolved to obtain a polymer / lithium salt solution.
[0181] (2) Film casting process: ZIF-8 nanofibers are covered on a polytetrafluoroethylene plate, and then the polymer / lithium salt solution is dripped into the nanofibers and allowed to stand in an argon glove box for 30 min to form a film. After the film is formed, it is placed in a 60°C vacuum drying oven to dry and remove the solvent to obtain a SPE@ZIF-8 composite polymer electrolyte membrane.
[0182] Comparative Example 2
[0183] This example provides a method for preparing a polymer electrolyte membrane, which comprises the following steps:
[0184] 1. Raw material preparation: polymer electrolyte matrix: polyethylene oxide (PEO); lithium salt: lithium trifluoromethanesulfonyl imide (LiTFSI); solvent: acetonitrile (ACN), used to dissolve PEO-based polymer.
[0185] 2. Formula ratio: The mass ratio of PEO and LiTFSI is as follows: PEO:LiTFSI=1:1.
[0186] 3. Preparation steps:
[0187] (1) Preparation of solution: PEO is dissolved in acetonitrile and stirred to form a polymer solution; then, LiTFSI lithium salt is added to the solution according to a proportion and stirred until the lithium salt is completely dissolved to obtain a polymer / lithium salt solution.
[0188] (2) Film casting process: The polymer / lithium salt solution is dripped into a polytetrafluoroethylene plate and allowed to stand in an argon glove box for 30 minutes to form a film; after the film is formed, it is placed in a 60°C vacuum drying oven to dry and remove the solvent to obtain the polymer electrolyte membrane in this example, that is, the PEO-based polymer electrolyte membrane.
[0189] Performance Testing
[0190] (1) Microscopic morphology test
[0191] The surface morphologies of ZIF-8 prepared in Comparative Example 1, ZIF-8@Ti prepared in Example 1, and ZIF-8@V prepared in Example 2 were observed by scanning electron microscopy (SEM). The surface morphology of ZIF-8@Ti prepared in Example 1 is shown in FIG. Figure 1 As shown by Figure 1It can be seen that the ZIF-8@Ti product has a uniform particle size and good dispersibility. In addition, the SEM image shows that the ZIF-8@V product prepared in Example 2 and the ZIF-8 prepared in Comparative Example 1 also have a uniform particle size and good dispersibility.
[0192] Transmission electron microscopy (TEM) was used to observe the internal structures of ZIF-8 prepared in Comparative Example 1, ZIF-8@Ti prepared in Example 1, and ZIF-8@V prepared in Example 2, especially the distribution of titanium atoms and vanadium atoms in the ZIF framework. TEM results show that titanium atoms and vanadium atoms are uniformly dispersed in the ZIF-8 framework without obvious agglomeration.
[0193] Spherical aberration electron microscopy was used to characterize the single atoms of ZIF-8@Ti and ZIF-8@V products. Figure 2 (a) As shown in the spherical aberration electron microscopy image, the titanium single atom in the ZIF-8@Ti product and the vanadium single atom in the ZIF-8@V product are uniformly dispersed in the ZIF-8 framework and have high stability. Synchrotron radiation X-ray absorption spectroscopy (XAFS) is used to further characterize the coordination environment of the titanium single atom or the vanadium single atom in the ZIF-8 framework. The XAFS test image of the titanium single atom is shown in Figure 2 (b) As shown in the XAFS test results, it can be seen that titanium and vanadium single atoms form a stable coordination structure with oxygen and nitrogen atoms in the ZIF-8 framework, which helps to improve the electrochemical performance of the composite polymer electrolyte membrane.
[0194] The surface morphologies of the ZIF-8 nanofibers prepared in Comparative Example 1, the ZIF-8@Ti composite nanofibers prepared in Example 1, and the ZIF-8@V composite nanofibers prepared in Example 2 were observed using a scanning electron microscope (SEM). Figure 3 As shown, it can be seen that ZIF-8, ZIF-8@Ti and ZIF-8@V are uniformly dispersed in the polymer-based nanofibers without particle agglomeration.
[0195] The surface morphology and cross-sectional microstructure of the polymer electrolyte membrane in Example 1 were characterized by SEM. The specific test results are as follows: Figure 4 (a) and Figure 4 As shown in (b), Figure 4 It can be seen that there is a good bonding interface between ZIF-8@Ti composite nanofibers and PEO polymer matrix.
[0196] (2) Electrochemical performance test
[0197] Ion conductivity test: The ionic conductivity of the composite polymer electrolyte membranes in Examples 1 to 2 and Comparative Examples 1 to 2 was tested by using an electrochemical impedance spectroscopy (EIS). The specific test method is as follows: the test was conducted at room temperature, and a symmetrical battery consisting of a lithium sheet sandwiching a polymer solid electrolyte membrane was used for the test. The test frequency range was 0.01 Hz to 1 MHz. The specific test results are shown in FIG. Figure 5 As shown, Figure 5 (a) is a graph showing the electrochemical stability window of the composite polymer electrolyte membranes in Examples 1-2 and Comparative Examples 1-2; Figure 5 (b) is a test graph of lithium ion conductivity of the composite polymer electrolyte membrane in Examples 1-2 and Comparative Examples 1-2. Figure 5 From the test results, it can be seen that the ionic conductivity of the ZIF-8@Ti composite polymer electrolyte membrane at room temperature is as high as 1.25mS cm-1, and the ionic conductivity of the ZIF-8@V composite polymer electrolyte membrane at room temperature is 0.9mS cm-1, which are significantly higher than the ionic conductivity of the ZIF-8 composite polymer electrolyte membrane (Comparative Example 1, whose ionic conductivity is 0.6mS cm-1) and the traditional PEO-based polymer electrolyte membrane (Comparative Example 2, whose ionic conductivity is 0.3mS cm-1).
[0198] Voltage stability window test: Cyclic voltammetry (CV) was used to test the LSV curves of the composite polymer electrolyte membranes in Examples 1 to 2 and Comparative Examples 1 to 2 respectively: The test was carried out by clamping the polymer electrolyte membrane between a lithium sheet and a stainless steel electrode, with a voltage scan range of -1V to 4.9V and a scan rate of 1mV s-1. The blank group was the PEO-based polymer electrolyte membrane in Comparative Example 2. The specific LSV test results are shown in FIG. Figure 6 As shown by Figure 6 It can be seen that in the voltage range of 2.5-6V, the composite polymer electrolyte membranes in Examples 1 to 2 exhibit more stable electrochemical properties in a wider voltage range and have better applicability in high voltage applications. Specifically, the voltage stability of the ZIF-8@Ti composite polymer electrolyte membrane is better than that of the ZIF-8@V composite polymer electrolyte membrane and the ZIF-8 composite polymer electrolyte membrane. The voltage stability window of the ZIF-8@Ti composite polymer electrolyte membrane is 1.25-4.9V, as high as 4.9V; the voltage stability window of the ZIF-8@V composite polymer electrolyte membrane is 1.25-4.7V, as high as 4.7V; the voltage stability window of the ZIF-8 composite polymer electrolyte membrane is 1.25-4.5V.
[0199] The lithium ion mobility of the SPE@ZIF-8@Ti composite polymer electrolyte membrane in Example 1 was tested, and the measured time-current curve was as follows: Figure 7As shown, the initial and steady-state EIS graphs of the SPE@ZIF-8@Ti composite polymer electrolyte membrane are shown in Figure 8 As shown by Figure 7 and Figure 8 It can be seen that the SPE@ZIF-8@Ti composite polymer electrolyte membrane in Example 1 has a high lithium ion mobility, and its lithium ion migration number is as high as 0.79, which has significant advantages in lithium ion conduction. In battery applications, it can provide higher ion conductivity, thereby improving the overall performance of the battery. It further shows that the polymer electrolyte membrane in the present invention can enhance the lithium ion transmission capacity while maintaining structural stability through the combination of titanium or vanadium metal single atoms and metal organic frameworks (ZIF-8, HOF, COF, etc.).
[0200] In summary, the voltage window and ionic conductivity of the composite polymer electrolytes in Examples 1 to 2 are significantly better than those in Comparative Examples 1 to 2, especially the SPE@ZIF-8@Ti composite polymer electrolyte membrane in Example 1, indicating that the present invention has broad application prospects in high voltage and high power applications.
[0201] (3) Thermal stability test
[0202] Burning test: used to evaluate the thermal stability of the polymer electrolyte membrane in Example 1 and Comparative Example 1. The test results are as follows: Fig. 9 As shown, Fig. 9 (a), (a1), (a2) and (a3) are graphs of the polymer electrolyte membrane in Comparative Example 1 after calcination for 5s, 10s, 20s and 30s, respectively; Fig. 9 (b), (b1), (b2) and (b3) are the graphs of the polymer electrolyte membrane in Example 1 after calcination for 5s, 10s, 20s and 30s respectively. Fig. 9 It can be seen that the ZIF-8@Ti composite polymer electrolyte membrane in Example 1 did not burn within 30 seconds, indicating its good flame retardant properties; while the ZIF-8 composite polymer electrolyte membrane in Comparative Example 1 burned within 30 seconds, indicating poor flame retardant properties.
[0203] Thermogravimetric analysis (TG): The TG test was used to evaluate the thermal stability of the composite polymer electrolyte membranes of Example 1 and Comparative Example 1. The test temperature range was from room temperature to 800°C, and the heating rate was 10°C / min. The specific test results are as follows: Fig.10 As shown by Fig.10 It can be seen that the ZIF-8@Ti composite polymer electrolyte membrane has no obvious mass loss below 200°C and still maintains good structural stability above 200°C, indicating that it has good thermal stability, which helps to improve the safety of the battery and shows that the polymer electrolyte membrane in the present invention can be used in high temperature environments.
[0204] Differential Scanning Calorimetry (DSC): DSC test was used to analyze the glass transition temperature (Tg) and crystalline melting point of the polymer electrolyte membranes in Comparative Examples 1 to 2 and Example 1. The test temperature range was -80°C to 80°C, and the cooling and heating rates were both 10K / min. The specific test results are shown in Fig.11 As shown. Fig.11 It can be seen that the ZIF-8@Ti polymer electrolyte membrane in Example 1 introduces titanium single atoms, which can significantly improve the T g , while maintaining good low temperature stability, specifically: the T g -52.2℃, T m is 71.5°C; the T g -50.8℃, T m is 69.5°C, and the T g -45.5℃, T m It is 65.2℃.
[0205] It can be seen from the TG and DSC test results that the introduction of ZIF-8@Ti and ZIF-8@V materials into the polymer electrolyte membrane significantly improves the thermal stability of the PEO-based polymer electrolyte membrane, especially the ZIF-8@Ti material, which can enable the polymer electrolyte membrane to maintain good structural stability at higher temperatures.
[0206] (4) Cyclic performance test
[0207] The polymer electrolyte membranes in Examples 1 to 2 and Comparative Example 1 are assembled together with lithium iron phosphate positive electrode, lithium metal negative electrode and electrolyte membrane into CR2032 button batteries. The specific composition of the battery includes: lithium iron phosphate (LiFePO4) positive electrode; lithium metal negative electrode; electrolyte membrane: ZIF-8@Ti polymer electrolyte membrane in Example 1, ZIF-8@V polymer electrolyte membrane in Example 2, and ZIF-8 material electrolyte membrane in Comparative Example 1; other components: stainless steel gaskets, springs, sealing rings and outer shells. The test conditions are: at room temperature (25°C), the rate performance test is carried out using the constant current mode, and the current densities are 1C, 2C, 5C and 10C respectively. The specific test results are as follows: Fig.12 As shown. Fig.12 It can be seen that the polymer electrolyte membranes in Examples 1 and 2 of the present invention enable the battery to have excellent capacity retention. Specifically, the capacity of the ZIF-8@Ti polymer electrolyte membrane in Example 1 at current densities of 1C, 2C, 5C and 10C is 160 mAh g -1 , 150mAh g-1 , 120mAh g-1, 80mAh g-1, significantly better than ZIF-8@V and ZIF-8 materials.
[0208] The polymer electrolyte membranes in Examples 1 to 2 and Comparative Example 1 were assembled with a lithium metal negative electrode and an electrolyte membrane into a symmetrical lithium / / lithium CR2032 button cell. The specific components of the battery include: a lithium metal negative electrode; an electrolyte membrane: the ZIF-8@Ti polymer electrolyte membrane in Example 1, the ZIF-8@V polymer electrolyte membrane in Example 2, and the ZIF-8 material electrolyte membrane in Comparative Example 1; other components: a stainless steel gasket, a spring, a sealing ring, and a shell. Then, at 0.2 mA cm -2 The cycle performance was tested at a current density of 10000 and a test temperature of 30°C. The specific test results are as follows: Fig.13 As shown, Fig.13 (a) is a time-voltage test curve of a battery assembled from the polymer electrolyte membranes in Examples 1 to 2 and Comparative Example 1; Fig.13 (b) and Fig.13 (c) in the middle is the local enlarged view at 100-110h and 1280-1300h respectively. Fig.13 It can be seen that the battery assembled with the polymer electrolyte membranes in Examples 1 and 2 still has high cycle stability when cycled for 1300 hours. In addition, the initial overpotential of the polymer electrolyte membrane in Example 1 is only 0.02V, and that of Comparative Example 1 is only 600 hours. This indicates that the polymer electrolyte membrane in the present invention has a longer cycle life and a more stable electrode interface, which is beneficial to extending the service life of the battery.
[0209] The polymer electrolyte membrane in Example 1 was assembled with a lithium iron phosphate positive electrode into a CR2032 button battery. The specific composition of the battery includes: a lithium iron phosphate (LiFePO4) positive electrode; a lithium metal negative electrode; an electrolyte membrane: Then a long cycle constant current charge and discharge test was carried out at a current density of 10C. The specific test results are as follows Fig.14 As shown. Fig.14 It can be seen that the ZIF-8@Ti composite polymer electrolyte membrane in Example 1 exhibits excellent cycle stability, with a capacity retention rate of 75% after 5000 cycles, far exceeding that of Comparative Examples 1 to 2, indicating its potential application value in high-power batteries and being able to meet the requirements of high-performance batteries for long cycle life.
[0210] The polymer electrolyte membrane in Example 1 and the lithium iron phosphate positive electrode were assembled into a CR2032 button battery. The specific components of the battery include: lithium iron phosphate (LiFePO4) positive electrode; lithium metal negative electrode; electrolyte membrane; other components: stainless steel gasket, spring, sealing ring and shell. The content of lithium iron phosphate positive electrode material is 0.9mg cm -2, 1.5 mg cm -2 、3.5mg cm -2 The constant current cycling performance of the assembled battery at 0.1C and 0.5C was tested at -30℃. The specific test results are as follows Fig.15 As shown. Fig.15 It can be seen that the battery assembled with the polymer electrolyte membrane in Example 1 shows excellent ionic conductivity and cycle performance at a low temperature of -30°C, and can cycle normally at both 0.1C and 0.5C, indicating that it has good wide temperature performance and has application potential in the development of low-temperature batteries.
[0211] The polymer electrolyte membrane in Example 1 and the lithium iron phosphate positive electrode are assembled into the solid-state soft-pack battery in Example 12. The specific components of the battery include: lithium iron phosphate (LiFePO4) positive electrode; lithium metal negative electrode; electrolyte membrane; other components: aluminum plastic film, pole ear. The weight of lithium iron phosphate is 60 mg, and then the constant current cycling performance of the battery is tested. The specific test results are as follows: Fig.16 As shown by Fig.16 It can be seen that the solid-state soft-pack battery assembled with the polymer electrolyte membrane in Example 1 has good cycle stability (specific capacity of 160 mAh g -1 , Coulombic efficiency is 99%, and the capacity retention rate after 100 cycles is close to 95%).
[0212] The polymer electrolyte membrane in Example 1 and the sulfur positive electrode were assembled into a CR2032 button battery, and the capacity-voltage curve of the battery was tested at a current density of 0.2C. The specific test results are as follows: Fig.17 The test results show that the initial discharge capacity of the battery is 1200mAh g -1 Then the polymer electrolyte membrane in Example 1 and the lithium cobalt oxide (LCO) positive electrode were assembled into a CR2032 button battery, and the capacity-voltage curve of the battery was tested at a current density of 0.1C. The specific test results are as follows: Fig.18 The test results show that the initial discharge capacity of the battery is 150mAh g -1 The polymer electrolyte membrane in Example 1 and the high nickel ternary material (NCM) positive electrode were assembled into a CR2032 button battery, and the capacity-voltage curve of the battery was tested at a current density of 0.1C. The specific test results are as follows: Fig.19 The initial discharge capacity of the battery is 180 mAh g -1 .Depend on Figure 17 to Figure 19 It can be seen that the battery using ZIF-8@Ti composite polymer electrolyte membrane exhibits good electrochemical performance under all cathode materials.
[0213] In summary, the composite polymer electrolyte membrane of the present invention has the following significant advantages and technical effects: (1) Significant improvement in room temperature lithium ion conductivity: By introducing ZIF-8@Ti, the room temperature lithium ion conductivity of the polymer electrolyte membrane of the present invention is increased from the conventional 10 -7 S cm -1 Increased to 10 -3 S cm -1 About, greatly improving the power performance and energy density of the battery. (2) Wider electrochemical stability window: Traditional PEO-based electrolyte materials usually have the problem of a narrow electrochemical stability window, which limits their application in high-voltage positive electrode materials. By introducing ZIF-8@Ti, the electrochemical stability window of the electrolyte membrane of the present invention is expanded to 1-5V, making it suitable for high-voltage positive electrode materials such as lithium cobalt oxide and high-nickel ternary materials. (3) Enhanced thermal stability and low-temperature performance: The composite polymer electrolyte membrane of the present invention remains stable above 200°C without obvious decomposition, ensuring its application safety in high-temperature environments. At the same time, the polymer electrolyte membrane still maintains a high ionic conductivity at a low temperature of -30°C, which is suitable for the development of low-temperature batteries.
[0214] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A polymer electrolyte membrane, characterized in that: It includes a nanofiber membrane, a polymer and an electrolyte salt; the polymer and the electrolyte salt are distributed in the nanofiber membrane; the nanofiber membrane contains a polymer fiber and a metal organic framework material loaded with metal single atoms; the metal single atoms are loaded in the metal organic framework material through coordination bonds, and the metal organic framework material is distributed in the polymer fiber.
2. The polymer electrolyte membrane according to claim 1, characterized in that: The metal organic framework material is selected from at least one of the following: ZIF organic framework materials, COF organic framework materials, and HOF organic framework materials; and / or, the polymer is selected from at least one of the following: polyethylene oxide, polyvinylidene fluoride, polyacrylate, polyether sulfone, polyvinyl alcohol, polyetherimide; And / or, the material of the polymer fiber is selected from at least one of the following: polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, poly-1,3-dioxolane, polyamide, polytetrafluoroethylene, and polycarbonate.
3. The polymer electrolyte membrane according to claim 1, characterized in that: The metal single atom is selected from at least one of titanium and vanadium.
4. The polymer electrolyte membrane according to claim 1, characterized in that: The mass ratio of the polymer to the electrolyte salt is 1:(0.15-2.4); And / or, the mass of the metal organic framework material carrying metal single atoms is 5.5-45% of the mass of the nanofiber membrane.
5. The polymer electrolyte membrane according to claim 1, characterized in that: The material of the polymer fiber includes polyacrylonitrile and polyvinylidene fluoride-hexafluoropropylene; the mass ratio of the polyacrylonitrile to polyvinylidene fluoride-hexafluoropropylene is (0.6-9):
1.
6. The polymer electrolyte membrane according to any one of claims 1 to 5, characterized in that: The thickness of the polymer electrolyte membrane is 20-30 μm.
7. The method for preparing a polymer electrolyte membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: mixing raw materials for preparing metal single atoms and raw materials for preparing metal organic framework materials to obtain metal organic framework materials loaded with metal single atoms; S2: preparing a nanofiber membrane by electrospinning a spinning solution comprising the metal organic framework material loaded with metal single atoms and a preparation material of the polymer fiber; S3: Filling the nanofiber membrane with a mixed solution including a polymer and an electrolyte salt to prepare the polymer electrolyte membrane.
8. The method for preparing a polymer electrolyte membrane according to claim 7, characterized in that: The electrospinning satisfies at least one of the following conditions: 1) The voltage of electrospinning is 10-20 kV; 2) The flow rate of the spinning solution is 0.013-0.1 mL / min; 3) The electrospinning receiving distance is 5 to 15 cm.
9. A battery, characterized in that: The polymer electrolyte membrane comprises the polymer electrolyte membrane according to any one of claims 1 to 6.
10. The battery according to claim 9, characterized in that: The battery includes a lithium metal battery, a sodium metal battery, a potassium metal battery, a sulfide solid-state battery, an oxide solid-state battery, and a soft-pack battery; And / or, the operating temperature of the battery is -30°C to 30°C.
Citation Information
Cited By
Preparation method of polytetrafluoroethylene composite film
CN121550865A